The effect of mesenchymal stem cell transplantation on the recovery of bladder and hindlimb function after spinal cord contusion in rats - Park, Won Beom (BioMed Central, 2010)
BACKGROUND: Mesenchymal stem cells are widely used for transplantation into the injured spinal cord in vivo model and for safety, many human clinical trials are continuing to promote improvements of motor and sensory functions after spinal cord injury. Yet the exact mechanism for these improvements remains undefined. Neurogenic bladder following spinal cord injury is the main problem decreasing the quality of life for patients with spinal cord injury, but there are no clear data using stem cell transplantation for the improvement of neurogenic bladder for in vivo studies and the clinical setting. The purpose of this study was to delineate the effect of human mesenchymal stem cell (hMSCs) transplantation on the restoration of neurogenic bladder and impaired hindlimb function after spinal cord contusion of rats and the relationship between neurotrophic factors such as brain derived neurotrophic factor (BDNF) and neurotrophin-3 (NT-3) and bladder and hindlimb functions. RESULTS: Modified moderate contusion injury were performed on the thoracic spinal cord of Sprague-Dawley rats using MASCIS impactor and hMSCs, human fibroblasts or phosphate-buffered saline were transplanted into injured spinal cord 9 days after injury for hMSC and two control groups respectively. Ladder test showed more rapid restoration of hindlimb function in hMSC group than in control group, but Basso, Beattie, and Bresnahan score and coupling score were not different significantly among hMSC and two control groups. Neurogenic bladder was not improved in either group. ED1 positive macrophages were significantly reduced in hMSC group than in two control groups, but ELISA and RT-PCR studies revealed BDNF and NT-3 levels in spinal cord and bladder were not different among hMSC and two control groups regardless the experimental duration. CONCLUSION: hMSC transplantation was effective in reducing inflammatory reaction after spinal cord contusion of rats but not sufficient to recover locomotor and bladder dysfunction. BDNF and NT-3 levels in the spinal cord and bladder were not increased 28 and 56 days after hMSC transplantation.